2019
DOI: 10.1177/2309499018820349
|View full text |Cite
|
Sign up to set email alerts
|

The inflamed biceps tendon as a pain generator in the shoulder: A histological and biomolecular analysis

Abstract: Introduction: The long head of the biceps (LHB) is often resected in shoulder surgery. However, its contribution to inflammatory processes in the shoulder remains unclear. In the present study, inflamed and noninflamed human LHBs were comparatively characterized for features of inflammation. Materials and methods: Twenty-two resected LHB tendons were classified into inflamed (n ¼ 11) and noninflamed (n ¼ 11) samples. For histological examination, samples were stained with hematoxylin eosin, Azan, van Gieson, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 30 publications
1
16
0
2
Order By: Relevance
“…Scale bar, 10 μm specimen suggesting that they are a regular constituent of LHBT. Meyelinated nerve fibers have been observed in the Achilles tendon of cat (Andres et al, 1985) but so far not in human tendons including the LHBT (Alpantaki et al, 2005, Boesmueller et al, 2017, Schmalzl et al, 2019, Achilles tendon (Ackermann et al, 2003, Alfredson et al, 2003, plantaris tendon (Spang et al, 2015), and proximal tendon of the flexors and extensors of the forearm (Ljung et al, 2004, Ljung et al, 1999a. Thus, our novel findings would prompt for further analyses to clarify whether myelination is a specific feature of the LHBT or is repeated in other human tendons.…”
Section: Unmyelinated As Well As Myelinated Axons Group In Nerve Fascmentioning
confidence: 74%
“…Scale bar, 10 μm specimen suggesting that they are a regular constituent of LHBT. Meyelinated nerve fibers have been observed in the Achilles tendon of cat (Andres et al, 1985) but so far not in human tendons including the LHBT (Alpantaki et al, 2005, Boesmueller et al, 2017, Schmalzl et al, 2019, Achilles tendon (Ackermann et al, 2003, Alfredson et al, 2003, plantaris tendon (Spang et al, 2015), and proximal tendon of the flexors and extensors of the forearm (Ljung et al, 2004, Ljung et al, 1999a. Thus, our novel findings would prompt for further analyses to clarify whether myelination is a specific feature of the LHBT or is repeated in other human tendons.…”
Section: Unmyelinated As Well As Myelinated Axons Group In Nerve Fascmentioning
confidence: 74%
“…A decline in the sliding of fascial tissues causes a picture of local inflammation, as shown for some types of cervicalgia [18]. An altered position of the collagen fibres, for example in a tendon, could change its mechanical function, creating pain but not inflammation [19]. If the layers and fascial orientations of an anatomical area lose the ability to move between them, the vectors of collagen fibrils will change, there will be an implementation of collagen deposition, creating a metabolic environment of inflammation and anomalous mechanical tension of the scaffold cell and extracellular matrix.…”
Section: Figure 1: the Statue Of The "Busto DI Donna Velata" By The Smentioning
confidence: 99%
“…Maintaining an optimal position of the collagen fibres, adapted to a specific anatomical structure (muscle, joint, visceral capsule, meninges, etc. ), means maintaining health [5,[19][20].…”
Section: Figure 1: the Statue Of The "Busto DI Donna Velata" By The Smentioning
confidence: 99%
“…However, few studies have verified whether inflammation is associated with LHBT tear. Recently, Schmalzl et al [21] reported that the gene expression of the proinflammatory cytokines of IL-1A, IL-1B, and TNF-α and of the catabolic enzymes MMP-1, − 3, − 9, and − 13 was upregulated, whereas the expression of the anti-inflammatory gene TIMP1 was downregulated in biceps tendinitis patients. The difference between this study and those previous studies is that this study newly focused on the inflammatory biomarker, hs-CRP, as an independent risk factor.…”
Section: Introductionmentioning
confidence: 99%